2005
DOI: 10.1081/txr-200057848
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Compounds in Tick and Mite Venoms (Saliva)

Abstract: Ticks and mites are bloodsucking ectoparasites containing anticoagulants as well as many other bioactive compounds. Because of their extremely small size, collection of venom (saliva) is very difficult. Therefore, the scientific study of tick and mite venoms is far less well developed than that of other venoms such as snake, scorpion, and bee. In this review article, anticoagulant components, paralytic toxins, and the effect of venom on the immune system are reviewed. Anticoagulants are discussed in three part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 129 publications
0
7
0
Order By: Relevance
“…The toxicity of ticks, which are hematophagic ectoparasites, comes from antigens in their saliva that modulate the host's immune response in order to facilitate blood feeding. Tick salivary anticoagulants are reported to act through either the inhibition of thrombin or inhibition of factor X activation [ 62 ]. Ixodes tick paralysis is a toxin-mediated type of acute flaccid paralysis caused by the presynaptic neurotoxin holocyclotoxin, which acts to inhibit acetylcholine release at the neuromuscular junction [ 63 65 ].…”
Section: Venom Pathogenesis and Poisoning In Australiamentioning
confidence: 99%
“…The toxicity of ticks, which are hematophagic ectoparasites, comes from antigens in their saliva that modulate the host's immune response in order to facilitate blood feeding. Tick salivary anticoagulants are reported to act through either the inhibition of thrombin or inhibition of factor X activation [ 62 ]. Ixodes tick paralysis is a toxin-mediated type of acute flaccid paralysis caused by the presynaptic neurotoxin holocyclotoxin, which acts to inhibit acetylcholine release at the neuromuscular junction [ 63 65 ].…”
Section: Venom Pathogenesis and Poisoning In Australiamentioning
confidence: 99%
“…They act as 'local hormones' and regulate a plethora of physiological processes 31,48 . PGs are a group of well-studied blood-sucking related metabolites, and they have been discovered in many bloodsuckers, including ticks [25][26][27][28] , salmon louses 29,30 and forest leeches 31 . Among them, PGE2 is the most commonly found PGs in the secretions, and it has demonstrated prolonged parasitic feeding (anticoagulant), increased blood flow to the site of attachment (vasodilation), and/or evasion of host immune responses (immunomodulator).…”
Section: Discussionmentioning
confidence: 99%
“…It has been also reported that PGE2 could inhibit wound healing by recruiting fibroblasts to the feeding lesion 27 . In addition to PGE2, PGF2 alpha was also commonly detected in bloodsuckers with reported functions of vasodilation, platelet aggregation inhibition, anti-inflammation, and pain alleviation 25, 31 . In this study, we have detected another two PGs, i.e., PGJ2 and PGE3, in lamprey buccal gland.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, sand flies contain a potent vasodilator (maxadilan) that acts via the PAC1 receptor [21,22], and horse fly disintegrins inhibit platelet aggregation like those from snake venoms [23]. Interestingly, tick prostaglandins constrict blood vessels [24]. The maintenance of blood flow during feeding is a major rate limiting step and challenge for blood feeders to overcome.…”
Section: Introductionmentioning
confidence: 99%